Evaluation of oral brush liquid-based cytology for oral squamous cell carcinoma: a comparative study of cytological and histological diagnoses at a single center - Katsutoshi Kokubun; Kei Nakajima; Kei Yamamoto; Yoshihiko Akashi; Kenichi Matsuzaka (BMC, 2023)
Abstract Purpose Liquid-based cytology is highly useful in oral cytology. However, there are only few reports on the accuracy of this method. The current study aimed to compare oral liquid-based cytological and histological diagnoses and to evaluate items that should be considered in oral cytological diagnosis for oral squamous cell carcinoma. Methods We included 653 patients who underwent both oral cytological and histological examinations. Data on sex, specimen collection region, cytological and histological diagnoses, and histological images were reviewed. Results The overall male-to-female ratio was 1:1.18. The tongue was the most common specimen collection region, followed by the gingiva and buccal mucosa. The most common cytological examination result was negative (66.8%), followed by doubtful (22.7%) and positive (10.3%). The sensitivity, specificity, positive predictive value, and negative predictive value of cytological diagnosis were 69%, 75%, 38%, and 92%, respectively. Approximately 8.3% of patients with a negative cytological diagnosis had a histological diagnosis of oral squamous cell carcinoma. Furthermore, 86.1% of histopathologic images of cytology-negative squamous cell carcinomas exhibited well-differentiated keratinocytes lacking atypia on the surface. The remaining patients developed recurrence, or they had low cell counts. Conclusion Liquid-based cytology is useful in screening oral cancer. However, a cytological diagnosis of superficial-differentiated oral squamous cell carcinoma is occasionally inconsistent with the histological diagnosis. Therefore, histological and cytological examinations should be performed if tumor-like lesions are suspected clinically.